Effect of Two Instructional Strategies on Students’ Achievement at Selected Abstract Concepts : A Case Study on Biology Learning in Kwara State, Nigeria - Adewumi, Gabriel Segun; Akanbi, Adejoke Arinlade; Muraina, Kamilu Olanrewaju (The Indonesian Institute of Science and Technology Research, 2024)
This study determined the effects of two instructional strategies (Project and Inquiry) on students’ achievement in selected abstract concepts of Biology. The study adopted the pretest-posttest control group, a quasi-experimental design. 120 SS II Biology students from six co-educational schools in two Local Government Areas (LGAs) of Kwara state were randomly selected. Participants were randomly assigned to treatment groups. The instruments used were: the Biology Student Achievement Test (r=0.88) and Teachers Instructional guides on Project and Inquiry strategies. Two hypotheses were formulated and tested at a 0.05 level of significance. The data collected were analyzed using analysis of covariance, the treatment had a significant main effect on students’ achievement on some selected abstract concepts in Biology(F(2, 107) =12.061; p<0.05, partial η2 = 0.184). Project strategy (PS) treatment group 1 has the highest adjusted mean achievement scores (x ̅=23.21) than those in the Inquiry Strategy (IS) treatment group11 (x ̅=17.81) and the students in the Conventional Strategy (CS) control group have the lowest adjusted mean achievement scores (x ̅=17.20). This order is represented as PS >IS > CS. The male students showed greater improvements in mean gain of achievement scores by 21.94 and female students by 17.13. Based on the findings Project and Inquiry strategies should be adopted for the improvement of students’ achievement in abstract concepts in biology.